2014
DOI: 10.1161/circep.113.000999
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Features and Prevalence of Bilateral Bundle-Branch Delay

Abstract: ElectrocardiogramsDuring electrophysiology study or device implantation, the surface ECG was monitored continuously and stored on a computer-based digital recording system (LabSystemPro, Bard Electrophysiology, Lowell, MA).© 2014 American Heart Association, Inc. Original ArticleBackground-Definitive diagnosis of bilateral bundle-branch delay/block may be made when catheter-induced right bundlebranch block (RBBB) develops in patients with baseline left bundle-branch (LBB) block. We hypothesized that a RBBB patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…Lenègre also reported similar findings of severe damage in RBB and LBB in patients with MBBB pattern. 6 Tzogias et al 7 in their study of patients who developed RBBB from catheter induced trauma to the right bundle branch during right heart catheterization, having divided the patients into normal, left anterior or posterior fascicular block and left bundle branch block group based on their background ECG morphology. They reported that MBBB pattern (RBBB in lead V1 with absent S wave in leads I and aVL) was seen only among the group with background LBBB among the 3 groups, while the remaining groups developed the typical RBBB pattern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lenègre also reported similar findings of severe damage in RBB and LBB in patients with MBBB pattern. 6 Tzogias et al 7 in their study of patients who developed RBBB from catheter induced trauma to the right bundle branch during right heart catheterization, having divided the patients into normal, left anterior or posterior fascicular block and left bundle branch block group based on their background ECG morphology. They reported that MBBB pattern (RBBB in lead V1 with absent S wave in leads I and aVL) was seen only among the group with background LBBB among the 3 groups, while the remaining groups developed the typical RBBB pattern.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 They may require permanent pacemaker insertion. 7,14 From a Brazilian registry, MBBB was associated with an estimated 4-year mortality and pacemaker insertion ratio of 41.4% and 38.9%, respectively. 16 MBBB sometimes present with syncope due to complete AV block necessitating pacemaker insertion.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…An atypical RBBB ECG pattern with absent or minimal S waves in leads I and aVL, also referred to as bilateral bundle-branch delay/block, was noted after RBB ablation ( Figure 3B ). 6 After ablation, repeat ventricular stimulation showed no inducible ventricular arrhythmias and the patient's ICD was reprogrammed to atrial sensed biventricular pacing. After over 4 years of follow-up no arrhythmias were detected by the ICD, and ultimately the patient underwent heart transplantation owing to worsening heart failure.…”
Section: Case Reportmentioning
confidence: 99%
“…In the setting of a pre-existing LBBB, with the exception of bilateral bundle branch delay, the onset of supra-VT would not result in narrowing of the QRS complex. 2 The relatively narrow QRS duration could be explained by the presence of VT involving electrical capture of the His-Purkinje system. In our patient's case, the VT must have entered the His-Purkinje system below the site of LBBB, with conduction down the Purkinje fibers resulting in a narrow QRS complex.…”
mentioning
confidence: 99%